Cardiovascular disease among women with and without diabetes mellitus and bilateral oophorectomy. Issue 3 (June 2015) - Appiah, Duke; Winters, Stephen J.; Allison, Matthew A.; Baumgartner, Richard N.; Groves, Frank D.; Myers, John A.; Hornung, Carlton A.
Abstract: Aims: Women with type-2 diabetes (DM2) are at high risk of cardiovascular disease (CVD) which may be partly due to increased ovarian androgen production. Since the association of bilateral oophorectomy (BSO) with CVD remains controversial, we evaluated whether BSO is inversely associated with CVD among DM2. Methods: Data were obtained from a national sample of 9599 postmenopausal women. Adjusted estimates and 95% confidence intervals (CIs) were calculated using logistic and Cox regression. Results: At baseline 2426 women had type-2 diabetes, of whom 580 had BSO. DM2 had adverse CVD risk profiles compared to women without diabetes, as did women with BSO with or without diabetes compared to those with intact ovaries. In DM2, BSO was positively associated with prevalent CVD (odds ratio: 1.63, 95%CI: 1.16–2.30). However, the higher odds were limited to women who had BSO before age 45 years (OR: 2.11, CI: 1.45–3.08). During a mean follow-up of 12.7 years, BSO in DM2 was positively associated with CVD mortality (hazard ratio: 2.23, CI: 1.25–3.99). Among women with BSO, those with family members who had MI before age 50 had elevated odds of CVD (OR: 2.29, CI: 1.56–3.37) compared to those without such family history (OR: 0.90, CI: 0.67–1.20), P interaction = 0.04. Conclusions: The risk of CVD is increased not decreased with BSO in DM2. Further, we propose that the association of BSO and CVD in young women with diabetes may partly reflect genetic susceptibility to CVD rather than an effect of ovarian hormones.